Analysis of Different Device Interactions in a Virtual Reality Task in Individuals With Duchenne Muscular Dystrophy—A Randomized Controlled Trial - de Freitas, Bruna Leal; da Silva, Talita Dias; Crocetta, Tânia Brusque; Massetti, Thais; de Araújo, Luciano Vieira; Coe, Shelly; Dawes, Helen; Caromano, Fatima Aparecida; Monteiro, Carlos Bandeira de Mello (Frontiers in Neurology, 2019)
There is a need to support individuals with Duchenne Muscular Dystrophy (DMD) to achieve optimal functionality in everyday life and with meaningful tasks and activities, throughout stages of the disease progression. Thus, technological developments have created an exciting opportunity for the use of affordable virtual reality (VR) systems with different kinds of interaction devices, providing an efficient and fun tool for enabling improvement in motor performance. Objective: To compare performance on a virtual task using interfaces with and without physical contact in order to identify functionality by using different devices in individuals with DMD. Methods: One hundred and twenty male individuals took part on this study: 60 with DMD with a mean age of 16 ± 5 (range 9–34 years old) and 60 without DMD in the control group (CG) matched by age. Participants were divided into three groups of 20 individuals each which performed a virtual task in three different interfaces: Kinect®, computer Touch Screen and Leap Motion®, in a cross over design in which all participants used all devices. Motor impairment in the DMD group was measured by using the Motor Function Measurement and Vignos scales. Results: All participants improved performance through practice, regardless of the interface used, although the DMD group had a continuous lower performance compared to the CG. In addition, the DMD group obtained a significant better performance with Leap Motion interface compared to the other interfaces, while the CG presented better performance on Touch Screen interface. Conclusion: Leap Motion provided better performance for individuals with DMD due to enablement of distal muscle function and ease of instrument adjustment using the virtual interface. Therefore, this type of interface should be encouraged for promoting functionality on general tasks using computer systems. Clinical Trial register number: NCT02891434.